Impact of federalization for health financing and workforce in Nepal - Meifang Chen; Dinesh Thapa; Rongxiao Ma; Daniel Weissglass; Hao Li; Biraj Karmachaya (BMC, 2023)
Abstract The adoption of its 2015 constitution has converted Nepal to a federal government while simultaneously resulted in significant reforms of the health system in Nepal in terms of both structure and commitment. In this commentary, we review evidence ranging from health financing to health workforce development to show that the impact of federalization on Nepal's health system and its efforts to achieve equitable and affordable universal health care have been mixed. On the one hand, careful efforts of the federal government to support subnational governments during the transition appears to have avoided serious disruption, subnational governments have successfully taken on the financial burden of the health system, and increase subnational control has allowed more flexible adaptation to changing needs than might have otherwise been possible. On the other hand, financing resource and ability disparities across subnational governments contributes to significant disparities in workforce development, and subnational authorities appear to have underestimated significant health issues (e.g. NCDs) in their budgets. We then provide three recommendations to improve the success of the Nepalese system: (1) to assess whether the services covered by health financing and insurance schemes like the National Health Insurance Program adequately address the needs of the rising burden of NCDs in Nepal, (2) to set clear minimum requirements on key metrics for subnational health systems, and (3) to extend grant programs to address resource disparities.